Prevention Is Better Than Cure - Hamid, Fadzilah Abd; Hamzah, Fathiiah (International Journal of Human and Health Sciences (IJHHS), 2024)
Health Promotion should be advocated at all times. The definition of health is the state of physical, mental and spiritual well-being, not merely the absence of disease and infirmity. Breastfeeding is the basic foundation of a person's health. It provides a well balanced diet during infancy, and contains antibodies preventing human diseases. More important is it helps to meet the psychological aspects of the individual through the senses of touch, sight, smell and hear. Health of a family starts as early as the future mother (the girl) reaches puberty. The girl should be guided to be hygienic at all times especially the perineal care. Excessive leukorrhea should be constantly washed otherwise can cause urinary tract infections which can lead to salpingitis and even infertility. During delivery all efforts should be made to ensure the Apgar score of the newborn is 8 and above. This can facilitate academic excellence. Obesity should be prevented from childhood. Diet intake should follow the recommended Ministry of Health menu from the weaning diet of the infancy, adolescent, and adult till that of the elderly. Body mass index at 22 years old should be maintained till old age. Excessive stress should be avoided, difficult issues handled from time to time. Manual activities not only help one to be physically fit but also helps reduce stress. Social skills should be attained to make life more enjoyable. Laughing with family and friends is the best medicine. Our vertical relationship with Allah the creator is of the utmost importance. Prayers in the midmorning have proved to ensure good physical health - long prostration causes increased immunity. Proper ‘Makhraj’ of Quran reading contributes to facial exercises. Regular fasting on Mondays and Thursdays and ‘Ayamul Bidh’ improve the digestive system, thus preventing other health problems. Leaning ‘taranum’ can be enjoyed as a skill to reactivate the brain cells. The above holistic care, if practised consistently, would be able to ensure quality of life. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S35